DIGITAL TRANSFORMATION IN THE REAL ESTATE MARKET: HOW APPS ARE REDEFINING TRANSACTIONS AND ACCESSIBILITY - da Costa, Monique Cristina Rocha (Revista Sistemática, 2024)
In recent years, real estate brokerage apps have profoundly transformed the market, offering a more convenient, accessible, and efficient experience for both clients and agents. These digital platforms streamline the entire process of buying, selling, and renting properties, from research to closing, with tools such as detailed filters, high-resolution photos, videos, and virtual tours. The main advantage of these apps is the ability to search for properties anytime and anywhere, making the research process more efficient and reducing the need for in-person visits. Transparency is also a key strength of these platforms, which provide detailed information about properties, such as history, tax values, and financing estimates. Many apps also offer financial simulations to help clients assess their purchasing power. Communication between clients and agents has been improved with features like instant messaging and real-time notifications, accelerating the process and enhancing the user experience. Furthermore, digitization has enabled remote transaction closures using digital signatures and secure cloud storage, eliminating the need for physical relocation and making the process easier for those buying or renting remotely. Recent studies highlight how these innovations have improved the accuracy and transparency of real estate transactions through the use of artificial intelligence and digital database systems. The constant evolution of these apps promises an even more dynamic future for the real estate market, making it more accessible and efficient.